Sustainable Repurposing of Coffee By-Products: A Systematic Review of Bioactive Potential and Safety Risks - Aurum, Fawzan Sigma; Wibowo, Nendyo Adhi; Purwanto, Eko Heri; Wanita, Yeyen Prestyaning; Novitasari, Erliana; Amri, Aldicky Faizal; Yulianti, Yulianti; Karim, Mirwan Ardiansyah; Zainal, Putri Wulandari; Praseptiangga, Danar (Pandawa Institute, 2026)
This systematic review (2020–2025) synthesizes evidence from recently peer-reviewed studies to evaluate the sustainable repurposing of coffee by-products. The analysis addresses four research questions (RQs) focused on chemical composition, application, safety, and sustainability. Quantitative results for RQ1 (bioactive composition) confirm that 100% of the studies identify high phytochemical density, notably chlorogenic acids, caffeine, and melanoidins. Specific benchmarks include caffeine levels up to around 31 mg/g in silverskin and a 6–10% lipid fraction in spent coffee grounds (SCG). For RQ2 (the application of the by-product) the evidence primarily concentrates on bakery products (bread, biscuits, gluten-free formulations) and beverages (teas, kombucha, soft drinks), followed by dermato-cosmetic formulations like creams and exfoliants. Critically, RQ3 (safety issues) reveals a significant evidence gap; while 10 hazard categories including mycotoxins and acrylamide were identified, standardized toxicological data remains fragmented. Similarly, RQ4 (sustainability aspect) remains conceptually strong but empirically weak, with only less than15% of studies providing quantitative indicators such as life cycle assessment (LCA) metrics. Despite qualitative support for circular economy integration, the lack of standardized safety protocols and human clinical trials limits regulatory approval. This manuscript integrates compositional value, real-world functionality, regulatory-relevant safety (including microbiology), and decision-useful sustainability into a single PRISMA-guided evidence map, making it a translational assessment rather than a descriptive inventory.